Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1038/s41467-018-05251-z
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting myosin-5B mechanosensitivity and calcium regulation at the single molecule level

Abstract: Myosin-5B is one of three members of the myosin-5 family of actin-based molecular motors. Despite its fundamental role in recycling endosome trafficking and in collective actin network dynamics, the molecular mechanisms underlying its motility are inherently unknown. Here we combine single-molecule imaging and high-speed laser tweezers to dissect the mechanoenzymatic properties of myosin-5B. We show that a single myosin-5B moves processively in 36-nm steps, stalls at ~2 pN resistive forces, and reverses its di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 80 publications
0
31
0
Order By: Relevance
“…Similarly, Ca 2+ -induced relief of auto-inhibition and the resulting ATPase activation and association with cargo has been observed for myosin Vb in vivo and in vitro [117]. Interestingly, although Ca 2+ does not directly affect the activity of the motor of myosin V [21,118], it significantly impairs its processivity in vitro by inducing dissociation of CaM from one or more of the IQ motifs, and therefore compromising the stiffness of the neck [118][119][120]. Therefore, although Ca 2+ activates myosin V through release of the auto-inhibition, it also results in a mechanically compromised myosin.…”
Section: Regulation Within the Local Environment: Divalent Cationsmentioning
confidence: 64%
See 1 more Smart Citation
“…Similarly, Ca 2+ -induced relief of auto-inhibition and the resulting ATPase activation and association with cargo has been observed for myosin Vb in vivo and in vitro [117]. Interestingly, although Ca 2+ does not directly affect the activity of the motor of myosin V [21,118], it significantly impairs its processivity in vitro by inducing dissociation of CaM from one or more of the IQ motifs, and therefore compromising the stiffness of the neck [118][119][120]. Therefore, although Ca 2+ activates myosin V through release of the auto-inhibition, it also results in a mechanically compromised myosin.…”
Section: Regulation Within the Local Environment: Divalent Cationsmentioning
confidence: 64%
“…As described above, Ca 2+ has been shown to activate myosin Va in vitro [21,112], by releasing this auto-inhibition [113,114]. However, the in vivo relevance of such activation is still debated [117][118][119][120]. Instead, the interaction of myosin V with its cargo adaptors has been accepted as the main physiological mechanism of activation.…”
Section: Regulation By Binding Partners: Myosinmentioning
confidence: 99%
“…The present model can be extended to study the effects of the vectorial character of the applied load on the mechanics of dynein and myosin motors, since the load-velocity and -detachment rate behaviours of kinesins, dyneins, and myosins are similar [14][15][16][17]. This can help to understand the mechanics of collective function of different molecular motors, owing to the force-dependent interactions of the motors.…”
Section: (C) and 3(b)mentioning
confidence: 94%
“…They measured the vertical load component F z , where the horizontal component F x was resisting (<0, applied against the stepping direction). More recently, single-molecule optical trapping experiments [14][15][16][17] have studied the function of molecular motors under assisting loads F x (>0, applied in the stepping direction) as well. They have shown that the motors exhibit similar responses to the applied load direction: i) their velocity decreases with resisting loads, but changes slightly when the load is assisting, and ii) motors favor faster detachment rate under assisting loads than resisting ones.…”
Section: Introductionmentioning
confidence: 99%
“…A single a-catenin unfolds to bear force on actin Here, we used ultrafast force-clamp spectroscopy, a technique with sub-millisecond and sub-nanometer resolution based on laser tweezers 9,[15][16][17] , to dissect the mechanosensitivity of single mammalian a-catenin homodimers and a-b-catenin heterodimers. We first analyzed single purified recombinant a-catenin homodimers (named as a-catenin below).…”
mentioning
confidence: 99%